Trace elements: chrome, cobalt and nickel in patients with psoriasis vulgaris in different development phases. Part II. Dependence of concentration of chrome, cobalt and nickle in selected morphotic components and egesias on clinical character of disease - Kaszuba, Andrzej; Sielska, Halina; Zaczyńska-Janeczko, Julita; Seneczko, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
There was taken the correlation analysis of dependence chrome, cobalt and nickel concentration in red blood cells, plasma, urine, hair and nails in on psoriasis clinical parameters: age at beginning of disease, duration of disease, duration of last clinical recurrence, duration of last clinical remission, skin surface displaying clinical changes and area and severity of skin changes (PASI). The significant connection between compared group of parameters has been confirmed, however the general direction of these connections is not unequivocal.